Suspected Ovotesticular Disorders of Sexual Differentiation in a Phenotypic Male With Ambiguous Genitalia, Light Menstrual Flow, and Synchronous Bilateral Dysgerminoma: A Case Report From Ethiopia - Melkamu Siferih; Tesfaye Negasa; Muluken Yifru; Adane Sisay; Genetu Tadele; Tajudin Adem; Mikias Gebrie; Worku Taye (Case Reports in Pediatrics)
Conclusion: Ovotesticular DSD with bilateral dysgerminoma is exceedingly rare and poses significant diagnostic and therapeutic challenges. Early diagnosis, multidisciplinary management, and timely oncologic intervention are crucial for optimizing patient outcomes, especially in resource-limited settings. This case underscores the critical need for heightened awareness, improved access to karyotyping, genetic and hormonal assessments, and long-term follow-up for individuals presenting with ambiguous genitalia and atypical pubertal development.